Smart Food Test: Praktikum Sederhana Uji Zat Makanan untuk Meningkatkan Keterampilan Proses Sains Siswa SMA - Fakhrah Fakhrah; Ayu Rahmi; Fitriani, Henni; Unaida, Ratna; Fatmi, Nuraini; Nufus, Hayatun (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2026)
This Community Service (PkM) activity aims to improve high school students' science process skills through simple food substance testing practicums based on direct experiments. The problems faced by partners are students' low understanding of the concept of food substances and the less than optimal implementation of Biochemistry practicums in schools due to limited laboratory facilities. The method of implementing the activity uses a participatory, educational, and learning-by-doing approach which is implemented through the preparation stage, material socialization, practicum, mentoring discussions of practicum results, and activity evaluation. The practicum was carried out by testing carbohydrate and protein content using simple materials that are easily obtained in the surrounding environment. The activity evaluation was carried out through pretests and posttests of science process skills and participant response questionnaires. The results of the activity showed an increase in students' science process skills after participating in the practicum, especially in understanding the concept of food substances, making observations, analyzing experimental results, and drawing scientific conclusions. In addition, the participant response to the activity was in the very good category because the practicum activity was considered interesting, interactive, and able to increase student interest and learning activity. Through this activity, students gained direct experience in applying scientific methods so they were able to improve critical thinking, communication, collaboration, and problem-solving skills. Thus, simple experimental-based food substance testing practicums are effectively used as an effort to improve science process skills and the quality of Biochemistry learning in high school.